Projections of workforce requirements for public acute hospitals in Ireland, 2019-2035: A regional analysis based on the Hippocrates model - Conor Keegan; Aiofe Brick; Abián García-Rodríguez; Leonie Hill (The Economic and Social Research Institute (ESRI), 2022)
This is the fourth report to be published applying the ESRI's Hippocrates healthcare projection model. Previous analyses have applied Hippocrates to estimate baseline utilisation and expenditure for a range of health and social care services and to provide national projections of demand, capacity and expenditure. The analysis undertaken in this report, funded by the Health Service Executive, necessitated two important extensions to the Hippocrates model: extending it to project workforce requirements, and providing these projections at a regional level. We present regional workforce projections both in terms the current Hospital Group configuration and the new integrated Regional Health Areas. Workforce projections are considered over the medium term, between 2019 and 2035, and for a selected set of staff categories directly involved in patient care: medical staff, nursing and midwifery staff, healthcare assistants and health and social care assistants, and five health and social care professions (dietitians, occupational therapists, physiotherapists, speech and language therapists, and social workers).
Keywords: 330